Sosialisasi Potensi Pengembangan Kuliner Olahan Ikan untuk Meningkatkan Perekonomian Masyarakat - Magfirahtul Jannah; Nur Mustaqimah; Nurul Fajryani Usman (Damhil: Jurnal Pengabdian kepada Masyarakat, 2022)
Fish as an important source of animal protein for humans is very easily damaged, so it must be processed immediately for consumption. People generally sell fish in fresh form or in smoked form. This community service activity aims to socialize the potential of developing fish-processed culinary products to improve society's economy. The activity was carried out in Bilungala Village, Bonepantai District, Bone Bolango Regency, Gorontalo Province. This activity uses the counseling method, including the delivery of material by the speakers, followed by discussion sessions and fish processing demonstration. Participants who were PKK women and Posyandu cadres in Bilungala Village were very enthusiastic and grateful for the materials and training provided because they broadened their horizons and knowledge, and increased their motivation to try to make culinary processed fish products independently at their respective homes.